(untitled) (Scientific journal of the Fergana State University, 2022)
The effect of the nature and concentration of solutions of various strong acids, as well as the activity of water on the swelling of cross-linked polyvinyl alcohol in solutions of these compounds has been studied. As a result of the experiments, the influence of ionic radii and anion hydration energy on the swelling process was proved.